Analysis of Salesperson Behavior on Using Retailer App (Case Study: Indosat Ooredoo Hutchison) - Robby Al Aziz; Togar Alam Napitupulu (Journal of Information System and Informatics, 2022)
The evolution of information technology affects many organizations in Indonesia, especially telco companies. Indosat Ooredoo Hutchison or more commonly known as PT Indosat, Tbk. or Indosat, a telco company in Indonesia has implemented a mobile application called Simpel for use by the salespeople to sell products. Currently, the app has been used by 60% of the users for less than 10 transactions in a month which resulted in only 9% of total revenue generated by the retailer app. This occurrence gave a challenge for Indosat to manage and increase the transaction count in the aforesaid app. This study aimed to analyze the factors influencing a salesperson’s decision to more frequently use Simpel to sell products. Every telco company can learn from this research to enhance app features better. The analysis is based on human behavior in information systems environment. The combination of UTAUT and other variables was used in this study. The total sample was obtained from 467 respondents who registered and used the app. Analysis were conducted using the structural equation models to learn the impact that performance expectancies, effort expectancies, social influence, facilitation conditions, and quality of sales applications have towards behavioral intention to use mobile app; and to learn the impact of behavioral intention, social influence, and facilitating conditions towards improving the sales app usage behavior.